UPACARA KEMATIAN PADA MASYARAKAT NAGARI TALUAK KECAMATAN LINTAU BUO KABUPATEN TANAH DATAR DALAM PERSPEKTIF HUKUM ISLAM - Siska Elasta Putri (Institut Agama Islam Negeri Batusangkar, 2020)
The death ceremony is one of the traditional ceremonies carried out by the community in Nagari Taluak, Lintau Buo District, Tanah Datar regency. The implementation of this ceremony began from the first day the body was buried until the next hundred and ten days. The problem arising is how does the Islamic law perspective view the implementation of this traditional death ceremony? The method used in this research is qualitative method. Data collection was carried out by participatory observation and in-depth interview. The research findings are (1) if the ceremony is carried out by praying together, in the sense that the priest presides and the others agree, then there is no prohibition, (2) if the ceremony is held by holding a banquet, where the family of the deceased cooks food even to slaughter cows or goats, the priests of the four and the scholars agree that the act is makruh, (3) but it is permissible if it aims only to entertain the guests with the intention only to glorify them.